Valorisation of digestate from biowaste through solid-state fermentation to obtain value added bioproducts: A first approach. (January 2019) - Cerda, Alejandra; Mejias, Laura; Rodríguez, Paula; Rodríguez, Alejandra; Artola, Adriana; Font, Xavier; Gea, Teresa; Sánchez, Antoni
Highlights: Biowaste digestate was assessed as a source for value added produced through SSF. Protease production of 66 ± 8 and 65 ± 3 U g −1 DM is obtained at 4 and 48 h respectively. External sugar (1%) and fat (10%) sources are required for biosurfactant production. Biopesticides from Bacillus thuringiensis were successfully obtained. A maximum spores production of 2.85 ± 0.22(10 7 ) CFU g −1 DM was achieved. Abstract: Digestate from biowaste was assessed as a potential source of bioproducts of commercial and industrial interest through solid-state fermentation. The targeted bioproducts were hydrolytic enzymes (cellulases and proteases from autochthonous microbiome), biosurfactants (sophorolipids produced from Starmella bombicola ) and biopesticides (produced from Bacillus thuringiensis ). Low cellulase production was observed within the range of 0.5–1.5 FPU g −1 DM while protease production showed two discrete peaks of 66 ± 8 and 65 ± 3 U g −1 DM at 3.5 and 48 h, respectively. Low sophorolipids production was also obtained, with a maximum yield of 0.02 g g −1 DM using hygienised digestate supplemented with external sugar and fat sources. Biopesticides produced by B. thuringiensis were successfully at 72 h of operation, reaching a maximum spore production of 8.15 ± 0.04 (10 7 ) CFU g −1 DM and 2.85 ± 0.22 (10 7 ) CFU g −1 DM using sterile and hygienised digestate, respectively. These biopesticides could contribute to the substitution of chemically produced pesticides, moving towards a sustainable digestate management in a circular economy scheme.